Adoption of Central Bank Digital Currencies and the Role of Change Management in Central Banks - Chandaramony, Khun (Digital Repository of Theses - SSBM Geneva, 2025)
Central Bank Digital Currencies (CBDCs) signify a revolutionary advancement in monetary systems; however, their successful deployment necessitates not only technical and regulatory readiness but also proficient strategic change management within central banks. This research proposal delineates a study investigating how central banks can manage internal organizational transformation to enable successful CBDC adoption. The study examines the significance of structured change management practices—such as leadership communication, staff training, and stakeholder engagement—in the implementation of Central Bank Digital Currencies (CBDCs) within traditionally conservative central banking contexts. There exists a significant deficiency in both research and practice concerning internal change management for Central Bank Digital Currency projects. Although substantial literature examines technological design, economic ramifications, and user acceptance of CBDCs, there is significantly less understanding regarding how central banks can navigate internal transformations to mitigate organizational resistance and guarantee project success. Addressing this deficiency is crucial because even a technically proficient CBDC may fail without the endorsement of employees, cultural preparedness, and effective change management. The study will utilize a mixed-methods approach within an explanatory sequential design. A quantitative survey of 200 central bank officials engaged in CBDC initiatives will ascertain dominant change management practices and their relationship with project outcomes. This will be succeeded by qualitative interviews with approximately 10 key stakeholders to obtain a more profound understanding of the execution of change strategies and to elucidate the quantitative findings. By synthesizing these methodologies, the research will cultivate a thorough comprehension of the internal factors affecting CBDC implementation. The anticipated contribution comprises a collection of empirically based recommendations for central banks and policymakers regarding the management of organizational change for CBDC adoption, thereby addressing a significant gap between technological innovation and institutional preparedness.